The role of individual variation in flowering and pollination in the reproductive success of a crepuscular buzz-pollinated plant - Soares, Natalia Costa [UNESP]; Maruyama, Pietro Kiyoshi; Staggemeier, Vanessa Graziele [UNESP]; Morellato, Leonor Patrícia Cerdeira [UNESP]; Araujo, Marcio Silva [UNESP] (Oxford Univ Press, 2021)
Background and Aims Plant individuals within a population differ in their phenology and interactions with pollinators. However, it is still unknown how individual differences affect the reproductive success of plants that have functionally specialized pollination systems. Here, we evaluated whether plant individual specialization in phenology (temporal specialization) and in pollination (pollinator specialization) affect the reproductive success of the crepuscular-bee-pollinated plant Trembleya laniflora (Melastomataceae). Methods We quantified flowering activity (amplitude, duration and overlap), plant-pollinator interactions (number of flowers visited by pollinators) and reproductive success (fruit set) of T. laniflora individuals from three distinct locations in rupestrian grasslands of southeastern Brazil. We estimated the degree of individual temporal specialization in flowering phenology and of individual specialization in plant-pollinator interactions, and tested their relationship with plant reproductive success. Key Results Trembleya laniflora presented overlapping flowering, a temporal generalization and specialized pollinator interactions. Flowering overlap among individuals and populations was higher than expected by chance but did not affect the individual interactions with pollinators and nor their reproductive success. In contrast, higher individual generalization in the interactions with pollinators was related to higher individual reproductive success. Conclusions Our findings suggest that individual generalization in plant-pollinator interaction reduces the potential costs of specialization at the species level, ensuring reproductive success. Altogether, our results highlight the complexity of specialization/generalization of plant-pollinator interactions at distinct levels of organization, from individuals to populations, to species.
Keywords: Campo rupestre; espinhaco range; individual networks; Melastomataceae; phenology; Serra do Cipo; Trembleya laniflora